ORAL HEALTH RELATED QUALITY OF LIFE OF GERIATRICS PATIENTS IN PESHAWAR - Shazia Makhdoom; Liaquat Ali Malik; Manzar Anwar Khan (Pakistan Oral & Dental Journal, 2021)
The aim of this study was to evaluate oral health related quality of life (OHRQoL) and its association with DMFT(Decayed, Missed and Filled Teeth) and types of prosthesis in geriatric patients seen at the above named hospital . This cross sectional study was conducted at medical OPD of KTH Peshawar from October 2019 to December 2019 by using Non-probability consecutive sampling method of 411 geriatric patients .All the participants were approached as per inclusion and exclusion criteria, after obtaining the written informed consent all the patients had an oral examination by single examiner followed by an interview through a validated questionnaire This questionnaire consists of demographics after this OHRQoL were assessed through OHIP-14 scale ,having Likert scoring, with higher scores indicating poor oral health related quality of life (lower OHRQoL) and vice versa. In OHIP-14 scale cut-off values for ‘good oral health (OH)’ with OHIP-14 score
Keywords: Geriatric patients; Oral Health Related Quality of Life; Oral Health Impact profile